Chebyshev Approximation of the Analytical Solution of Dirichlet Problem (Journal of Computational Mathematics, 1993)
In this paper linear programming method for minimax approximation is used to obtain an approximation to the analytical solution of a Dirichlet problem using the logarithmic potential function as an approximating function. This approach has the advantage of producing a better approximation than that using other solution of the potential equation as an approximating or basis function for a problem in $n=2$ dimensions.